Hemispheric asymmetry in human lateral prefrontal cortex during cognitive set shifting - Konishi, Seiki (The National Academy of Sciences, 2002)
Functional organization of human cerebral hemispheres is asymmetrically specialized, most typically along a verbal/nonverbal axis. In this event-related functional MRI study, we report another example of the asymmetrical specialization. Set-shifting paradigms derived from the Wisconsin card sorting test were used, where subjects update one behavior to another on the basis of environmental feedback. The cognitive requirements constituting the paradigms were decomposed into two components according to temporal stages of task events. Double dissociation of the component brain activity was found in the three bilateral pairs of regions in the lateral frontal cortex, the right regions being activated during exposure to negative feedback and the corresponding left regions being activated during updating of behavior, to suggest that both hemispheres contribute to cognitive set shifting but in different ways. The asymmetrical hemispheric specialization within the same paradigms further implies an interhemispheric interaction of these task components that achieve a common goal.